(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
In the process of forming a comprehensively developed personality, physical education plays one of the leading roles. However, the opinion is increasingly spreading among scientists that the existing system of physical education cannot fully satisfy the needs of society in terms of training specialists with a high level of adaptation to the requirements of modern life, readiness to fully fulfill professional requirements. This is reflected in a significant deterioration in the level of physical fitness (PFP) and the functional state of the body of student youth. Retrospective analysis of scientific literature shows that in order to solve the above-mentioned problem of physical education of student youth, new effective means and methods of physical education, new knowledge about the use of physical and psychological capabilities of the body in this field are needed. Therefore, in higher educational institutions, it is necessary to create all the necessary conditions for effectively teaching students a healthy lifestyle by means of physical culture and forming a positive attitude towards their own health, ensuring motor activity, instilling a love for physical exercises, creating conditions for physical exertion, a healthy lifestyle became the basis of further life activities and formed the general and professional culture of the personality of a modern specialist with a higher education. Emphasis should be placed on the particularity of the components of a healthy lifestyle, in particular nutrition, the ability to correctly determine one’s diet, choose healthy products and adequate methods of their preparation, balance food and adhere to the diet. The areas of students’ motivational and value attitude towards physical culture, healthy lifestyle, physical self-improvement, the need for regular physical culture and sports are considered. That is why the education system and, especially, higher educational institutions, as institutions that ensure the social development of the individual, in addition to special tasks, are assigned the task of preserving the physical, mental and moral health of students.